1995
DOI: 10.1152/ajpendo.1995.269.4.e731
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of metabolic consequences in the progeny of rats fed a HC formula in their early postnatal life

Abstract: First-generation (1-) male and female rat pups were either reared artificially on a high-carbohydrate (HC) or a high-fat (HF) formula or nursed by mother (MF) from day 4 and weaned onto a stock diet on day 24. 1-HC rats compared with sex-matched control rats (1-HF and 1-MF) were hyperinsulinemic and mildly obese by day 60. We investigated the effect of maternal hyperinsulinemia on the second generation (2-) by intragroup breeding. The 2-HC male and female rats were hyperinsulinemic on day 45, had significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 3 publications
4
56
0
Order By: Relevance
“…2 The growth pattern of HC rats in the second generation parallels that of first generation HC rats (35) (Fig. 1B).…”
Section: Nutritionally Induced Generational Effect On Metabolic Progrmentioning
confidence: 59%
See 1 more Smart Citation
“…2 The growth pattern of HC rats in the second generation parallels that of first generation HC rats (35) (Fig. 1B).…”
Section: Nutritionally Induced Generational Effect On Metabolic Progrmentioning
confidence: 59%
“…1B). Female rats fed an HC milk formula during their suckling period spontaneously transmitted their metabolic characteristics to their progeny without the pups themselves having to undergo any nutritional treatment (35). The second generation HC rats display hyperinsulinemia and an altered insulin secretory pattern within 48 h after weaning them onto laboratory chow on day 24.…”
Section: Nutritionally Induced Generational Effect On Metabolic Progrmentioning
confidence: 99%
“…Overfeeding in the neonatal period has been shown to produce second generation effects on glucose homeostasis (Laychock et al 1995, Vadlamudi et al 1995, Patel et al 2001, Srinivasan et al 2003.…”
Section: Postnatal Programmingmentioning
confidence: 99%
“…Earlier, we showed that the overlap of an altered nutritional experience in the form of a high-carbohydrate (HC) milk formula with the critical window of postnatal organ development in neonatal rat pups resulted in the establishment of the HC phenotype (chronic hyperinsulinemia and adult-onset obesity) in these rats (19,26). Because of fetal development in HC female rats, adult progeny demonstrated the same HC phenotype (29). Whether the adaptations that predispose the progeny for expression of the HC phenotype in adult life occur during fetal development in the HC intrauterine environment was not explored in the earlier study.…”
mentioning
confidence: 99%
“…The mere switch in the major source of calories from fat in rat milk to carbohydrate in the HC milk formula without alterations in total caloric intake results in the immediate onset of hyperinsulinemia, its persistence even after its withdrawal on postnatal day 24, and adult-onset obesity occurring in both male and female rats (9,10,28). A significant observation from these studies was that firstgeneration female rats (1-HC) that were artificially reared on the HC milk formula in their immediate postnatal period spontaneously transmitted the HC phenotype of chronic hyperinsulinemia and adult-onset obesity to their progeny (2nd generation HC; 2-HC) without the necessity for any dietary intervention in 2-HC rats (29). Cross-breeding experiments showed that only 1-HC female rats and not 1-HC male rats could effect this transfer to the progeny, indicating that it is the fetal development in the intrauterine environment of the 1-HC female rat that predisposes them for metabolic malprogramming (S. Vadlamudi, M. Srinivasan, and M. S. Patel, unpublished observations).…”
mentioning
confidence: 99%